Decomposition of Oil Palm Empty Fruit Bunches of Various Sizes Treated With Excelzyme - Habibullah, Fakhrul; Prawito, Priyono; Hasanudin; Widiyono, Heru; Purwanti, Sri (BPFP Universitas Bengkulu, 2025)
The rapid expansion of the palm oil industry has led to an increased accumulation of Oil Palm Empty Fruit Bunches (OPEFBs), creating significant environmental challenges due to their slow decomposition rate and high lignin content. This study investigates the decomposition of OPEFBs of varying sizes treated with Excelzyme, a commercial enzyme formulation designed to enhance lignocellulosic biomass degradation. The research was conducted using a 2 factor Completely Randomized Design (CRD), with Excelzyme dosages (250 mL, 375 mL, and 500 mL) and OPEFB sizes (unchopped, 2-5 cm, 1-2 cm, and <0.5 cm) as treatment factors. The decomposition process was evaluated based on temperature fluctuations, pH, total nitrogen, organic carbon, and lignocellulosic composition (hemicellulose, cellulose, and lignin) over an 8-week period. Results indicated that Excelzyme significantly influenced organic carbon reduction, hemicellulose degradation, and lignin breakdown, with higher dosages accelerating the decomposition process. The size of OPEFBs also played a crucial role, as smaller particle sizes facilitated microbial and enzymatic activity, leading to more efficient decomposition. Statistical analysis revealed significant interactions between enzyme dosage and OPEFB size, with the combination of 500 mL Excelzyme and <0.5 cm OPEFBs showing the highest decomposition rate. Temperature monitoring indicated a peak around week 5, suggesting optimal microbial activity and enzymatic breakdown at this stage. These findings highlight the potential of Excelzyme treatment in optimizing OPEFB decomposition, offering a sustainable approach to managing palm oil industry waste. The study contributes to improved biotechnological strategies for waste management and resource utilization, paving the way for enhanced agricultural sustainability and environmental conservation.